(untitled) (Eurasian Journal of Engineering and Technology, 2022)
Construction In the construction and pavement industries, sand is a primary raw material. These materials combine with gravel to form "aggregate" in concrete, Portland cement, asphalt, mortar, and plaster. Sand is mostly made up of tiny fragments of decomposed rocks, corals, or shells, which form when water or other environmental factors are present. Building materials like asphalt and concrete are bulked up with sand to give them more density, strength, and durability. It’s also a decorative element in landscaping. Metal casting molds are made with molds made of specific types of sand, just as glass is made with particular types of sand. Sand is one of the most widely used natural resources because it is used in many industries, such as construction, electronics, and plastics. The research examines the effects and consequences of the sand bulking phenomenon on construction. The bulking effect is greatest when the moisture content of sand is between 6 and 8 percent. Moisture content has a diminishing effect on this effect, and at around 15-20 percent, it becomes insignificant. All things being equal, fine sand (particles with a size range of 0.25 mm to 0.15 mm) bulks more quickly than coarse sand (particle size around 2mm). According to the sand’s fineness, bulking up to 30% of the original dry sand volume may be possible, but only 15% of the original wet volume.